Analysing the Shema in the Light of the Neurobiology of Virtue - Andy Mullins (Religions)
Moses’s great command, known to us as the Shema, taught the Jewish people that the great goal of one’s entire being must be love of God but that this outcome can be easily obscured in the face of distractions and competing pleasures. The task he describes may be understood as an exhortation to live and teach moral virtues, informed by faith in God: self-management of impulses and conditionings so that we can think clearly about the goals we pursue and love wisely. This study offers an analysis of the Shema through the lens of neurobiology. This approach supports a literal interpretation of the Shema to the extent that it provides a neurobiological explanation for the role of memory, positive emotion, and curated attention in establishing positive convictions and holding to them in the face of contrary stimuli. In doing so, it demonstrates that such applications of neurobiology can enrich our understanding of human behaviour because they offer insights into the internal dynamics at work in human choices and motivations, and into the need for coherence between our emotional responses and our convictions.